PENGARUH CAPITAL INTENCITY RATIO, FREE CASH FLOW, LEVERAGE, UKURAN PERUSAHAAN, KEPEMILIKAN INSTITUSIONAL, DAN KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2014-2017 - Sari Mayang Nurika; Rasuli M; Rofika Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study was conducted to determine the effect of capital intensityratio, free cash flow, leverage, firm size, institutional ownership, and managerialownership on earnings management. The population in this study aremanufacturing companies listed on the Stock Exchange during the period 2014-2017. The test tool used in this study is multiple regression using SPSS version25.Samples are used by purposive sampling method. The data used are secondarydata collected through the Indonesia Stock Exchange website. Companies thatmeet the sample criteria are 25 companies from 135 companies listed on the IDX.The variables studied were the effect of capital intensity ratio, free cash flow,leverage, firm size, institutional ownership, and managerial ownership to accountfor earnings management. The results of this study indicate that capital intencityratio, free cash flow, leverage, firm size have a significant effect on earningsmanagement.Whereas institutional ownership and managerial ownership do notaffect earnings management. Overall, capital intensity ratio, free cash flow,leverage, company size, institutional ownership, and managerial ownership ofearnings management amounted to 43.8%. While the remaining 56.2% isinfluenced by other variables not examined in this study.Keywords : Capital Intensity Ratio, Free Cash Flow, Leverage, Company Size,Institutional Ownership, and Managerial Ownership, and EarningManagement.